"Why Not Live There?" Two 1908 houses in Addington and Hataitai - Mulligan, Amanda; Wright, Gareth (Architectural History Aotearoa, 2019)
In 1908 two houses were erected. They were both long and narrow. They both featured "stick" style half-timbered decoration. They both featured typical joinery of the era - double-sash windows, four-panel doors and elegantly profiled skirtings. And both were the product of speculative builders capitalising on an expanding housing market. One house was built in Hataitai, Wellington. The other was built in Addington, Christchurch. In the early twentieth century, the introduction of electric trams and an associated tunnel through Mt Victoria led to out-lying settlements like Hataitai becoming densely populated suburbs. In 1908 Addington was already an established inner suburb, but intensification was underway as remaining pockets of farmland were subdivided for housing. This paper will compare and contrast the respective careers of the developers of these two homes: J. W. Easson – an ambitious builder and joinery factory owner who oversaw the construction of 600 houses in the capital between 1905 and 1914, and Frederick Crawford, a smaller-scale speculator who built 50 houses in Christchurch in the same period.